Analysis of the Hadith on the Tradition of Warding Of Disaster of the Banjar Tribe in Serdang Bedagai - Rizqa Amelia; Juli Julaiha P; Sri Ulfa Rahayu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The tradition of tolak bala (repelling evil) is a cultural practice aimed at warding off disasters or calamities. The Banjar people, who live in Serdang Bedagai, North Sumatra, maintain this tradition as part of their cultural heritage, which they preserve and uphold. This study aims to analyze the practice of tolak bala from the perspective of the hadith of the Prophet Muhammad (peace be upon him). Through the analysis of the hadith, elements that align with Islamic teachings and those that contradict them can be identified, particularly those related to aspects of shirk (polytheism), or beliefs that are inconsistent with monotheism. This study uses a descriptive qualitative approach with data sources from the field and literature review.